Analysing patterns of coordination and patterns of control during a maximal instep kick in association football using novel data visualisation techniques in vector coding - Needham, R. A.; Gosling, J. A.; Naemi, R.; Hamill, J.; Chockalingam, N. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to use novel data visualisations for profiling the coordination pattern, segmental dominancy and inter-data point range of motion (IDP-ROM) when utilising a modified vector coding technique. On group data, coupling angle mapping and segmental dominancy profiling noted similar coordination patterns between the thorax and pelvis during the maximal instep kick on the dominant (D) and non-dominant limbs (ND). However, time-series profiling of IDP-ROM of the dominant segment visually highlighted greater pelvis range of motion during the forward swing phase of the kicking leg for the D limb in comparison to the ND limb.